Probing the inflaton potential with SKA - Modak, Tanmoy; Plehn, Tilman; Röver, Lennart; Schäfer, Björn Malte (SciPost Physics Core, 2022)
SciPost Journals Publication Detail SciPost Phys. Core 5, 037 (2022) Probing the Inflaton Potential with SKA
Gesehen am 10.10.2022